Faktor-Faktor Yang Mempengaruhi Efektivitas Implementasi Anggaran Berbasis Kinerja (Studi Empiris pada Pemerintah Kabupaten Boyolali) - Setiani, Istiqomah; , Dr. Zulfikar, SE, M.Si (2017)
This research aimed to analyze the influence of human resources, organizational commitment, leadership style, rewards and sanctions. The population used in this study is The Structural Officials in the scope of the Agency, the Department and the Office of the Government of Boyolali, with the sample amounted to 56 employees. The collected data were analyzed using data analysis to test the quality of data and classical assumption test and hypothesis test. Testing the hypothesis in this study using multiple regression analysis with t-test, f-tets and the coefficient of determination. The results showed that the coefficient of determination obtained a value of 0,593 which means that 59,3% The effectiveness of the implementation of performance-based budgeting influenced human resources, organizational commitment, leadership style, rewards and sanctions. While 40.7% is explained by other variables outside this research model. Hypothesis test results showed that the human resources, organizational commitment, leadership style, rewards and sanctions affect the effectiveness of the implementation of performance-based budgeting.